Application of an experimental design methodology for the optimization of cosmetotextile impregnation process by β-cyclodextrin based microcapsules. Issue 2 (1st February 2023) - Ben Abdelkader, Maroua; Azizi, Nedra; Baffoun, Ayda; Bordes, Claire; Chevalier, Yves; Majdoub, Mustapha
Abstract: Neroline-loaded microcapsules based on β-cyclodextrin polyurethane material were fixed on cotton fabric using an impregnation technique. The process parameters were optimized so as to achieve a maximum microcapsules deposition and binding. Simultaneous evaluation and optimization of the effects of interdependent parameters was achieved using an experimental design based on response surface methodology. The selection of the mathematical model and its use for statistical analysis were done by the least squares method using the Minitab 19 software. The optimal impregnation conditions yielding a fabric mass gain of 8.56% are as follow: 21 g·L −1 for the microcapsules concentration, 31 g·L −1 for the polyurethane cross-linker concentration and 0.72 g·L −1 for the cationic surfactant concentration. The morphological and mechanical characterization, and air permeability evaluations of the resulting cosmetotextile fabric show the suitability of the process in terms of applicability and end-use properties.